Serious game for teaching and learning first aid - Sng, Guo Jie (2017)
This project is a study of the feasibility of the implementation of a serious game for teaching and learning first aid. Implementation of a serious game is a has been achieved by students in the past. However, a first aid serious game is unlike the previous students’ serious game projects which mainly focus on teaching an academic subject. Firstly, the availability of first aid domain experts is uncertain as there is no previous effort to secure the collaboration of industry partners in the field of first aid. Secondly, learning first aid requires participants to deal with human life and may have a strong emotional effect on the participants. As such, this project would mainly focus on securing collaboration for domain knowledge expertise and learning materials from potential industry partners in the context of Singapore as well as developing a prototype to validate the feasibility and effectiveness of a first aid serious game implementation.